Penerapan algoritma simulated annealing pada notifikasi informasi jadwal menggunakan RESTFUL api untuk rekomendasi jadwal asistensi di laboratorium komputer - Anggra Triawan; Muhammad Al Faruq (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2019)
In the current era of globalization, technology is needed in the quality of high school science. The quality of knowledge influences relevant knowledge, ways of teaching, a technology used, and planning of courses. At STIKOM there are many courses that require computer laboratories, where these courses will not be effective if taught in theory. Every one or more courses conducted by a computer laboratory are taught by a lecturer and a laboratory. Assistant, if the Lecturer cannot teach Lab. The assistant will replace as a teacher according to the instructions given by the Lecturer. The problem is the difficulty in determining a suitable time schedule for the Lab. Missing assistants, like Lab. Assistant who is still in college or has a job. Unequal distribution of subjects in each Lab. Assistant. Therefore we need a system to provide scheduling recommendations for lab assistants. Simulated Annealing Algorithm uses the input of the ability of time from each lab assistant. and is chosen based on the amount of energy added if selected in one course and if the same amount of energy will be chosen randomly. The results of the feasibility test questionnaire conducted obtained proper results on users with a percentage of eligibility of 76.3% and very feasible on system experts with a percentage of eligibility of 90%.